The novel R211Q POP1 homozygous mutation causes different pathogenesis and skeletal changes from those of previously reported POP1‐associated anauxetic dysplasia. Issue 5 (5th March 2020) - Abdulhadi‐Atwan, Maha; Klopstock, Tehila; Sharaf, Muna; Weinberg‐Shukron, Ariella; Renbaum, Paul; Levy‐Lahad, Ephrat; Zangen, David
Abstract: Processing of Precursor RNA 1 (POP1) is a core protein component shared by two essential closely related eukaryotic ribonucleoprotein complexes: RNase MRP (the mitochondrial RNA processing ribonuclease) and RNase P. Recently, five patients harboring mutations in POP1 have been reported with severe spondylo‐epi‐metaphyseal dysplasia and extremely short stature. We report a unique clinical phenotype resulting from the novel homozygous R211Q POP1 mutation in three patients from one family, presenting with severe short stature but only subtle skeletal dysplastic changes that are merely metaphyseal. The RNA moiety of the RNase‐MRP complex quantified in RNA extracted from peripheral lymphocytes was dramatically reduced in affected patients indicating instability of the enzymatic complex. However, pre5.8s rRNA, a substrate of RNase‐MRP complex, was not accumulated in patients' RNA unlike in the previously reported POP1 mutations; this may explain the uniquely mild phenotype in our cases, and questions the assumption that alteration in ribosomal biogenesis is the pathophysiological basis for skeletal disorders caused by POP1 mutations. Finally, POP1 mutations should be considered in familial cases with severe short stature even when skeletal dysplasia is not strongly evident.